2015
DOI: 10.1021/acs.jproteome.5b00388
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic Profiling Reveals Cancer Chemopreventive Effects of American Ginseng on Colon Carcinogenesis in ApcMin/+ Mice

Abstract: American ginseng (Panax quinquefolius L.) is one of the most commonly used herbal medicines in the West. It has been reported to possess significant antitumor effects that inhibit the process of carcinogenesis. However, the mechanisms underlying its anticancer effects remain largely unresolved. In this study, we investigated the cancer chemopreventive effects of American ginseng on the progression of high fat (HF) diet-enhanced colorectal carcinogenesis with a genetically engineered ApcMin/+ mouse model. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…A recent CE-TOFMS-based metabolomics study suggested that the metabolic profile of DEN model is effective to identify novel biomarkers for early diagnosis of human hepatocellular carcinoma (30). Indeed, inhibition of AA metabolic pathway has been recently reported to associate with the chemoprevention of high fat diet-enhanced colorectal carcinogenesis (41) and the apoptosis of hepatocellular carcinoma cells (42). Furthermore, significantly elevated content of AA was also reported in hepatocellular carcinoma patients compared with the healthy controls (11).…”
Section: Discussionmentioning
confidence: 99%
“…A recent CE-TOFMS-based metabolomics study suggested that the metabolic profile of DEN model is effective to identify novel biomarkers for early diagnosis of human hepatocellular carcinoma (30). Indeed, inhibition of AA metabolic pathway has been recently reported to associate with the chemoprevention of high fat diet-enhanced colorectal carcinogenesis (41) and the apoptosis of hepatocellular carcinoma cells (42). Furthermore, significantly elevated content of AA was also reported in hepatocellular carcinoma patients compared with the healthy controls (11).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time PCR was performed on a 7900HT RT-qPCR system (Applied Biosystems, Foster City, CA). The primers used for real-time PCR were described previously (24, 25). β -actin was used as an endogenous control.…”
Section: Methodsmentioning
confidence: 99%
“…The levels of cytokines IL-1β and IL-6 were quantified by ELISA (Life Technologies, Grand Island, NY) (24). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations